Automated Writing Evaluations in The ESL Classroom - Adetoyese, Oladiji Opeyemi (2023)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Oladiji Opeyemi Adetoyese entitled, “Automated Writing Evaluations in The ESL Classroom”, submitted in May 2023. Thesis advisor is Dr. Philip McCarthy and thesis co-advisor is Dr. Tammy Gregersen. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).